How can business buyers attract sellers' resources? Empirical evidence for preferred customer treatment from suppliers - Baxter, RA (Elsevier, 2012)
This paper describes a study that investigates what makes a buyer attractive to a seller in a business-to-business buyer-seller relationship and encourages the seller to commit to and invest resources preferentially in the relationship. The study helps answer the question, “What is it that the buyer needs to do to create this attractiveness?” The perspective is somewhat unusual in the marketing literature for two reasons. Firstly, because it investigates how the supplier perspective of customer financial attractiveness affects the attitudes and actions of the supplier towards the buyer, rather than taking the buyer’s perspective across the relationship. Secondly, the study has relationship attractiveness in terms of financial performance as an antecedent of its relationship constructs, whereas most relationship studies investigate performance as an outcome. The paper develops a model that proposes the seller’s perception of customer financial attractiveness, seller satisfaction, and seller commitment as drivers of the seller’s preferred customer treatment by allocation of resources to the relationship. The bases for the study’s model are the resource-based view of the firm, the industrial marketing and purchasing (IMP) models, and related resource-focused theoretical streams. The study finds support for the model in the analysis of survey data.
Keywords: Customer financial attractiveness; Rreferred customer treatment; Relationship; Resource investment; Supplier commitment; Supplier satisfaction